Macroeconomic challenges of fiscal decentralization in Latin America in the aftermath of the global financial crisis - Ter-Minassian, Teresa (UN ECLAC SantiagoCL, 2011)
Discusses how fiscal decentralisation is affecting macro-economic management in the main Latin American countries; and which reforms in the existing inter-governmental fiscal systems of those countries could help strengthen their fiscal sustainability, minimise the risk of pro-cyclicality at all levels of government and create "fiscal space" for active counter cyclical responses to economic shocks.